Endogenous tie formation mechanisms in a directed network generated by employee mobility - Francois Collet; Peter Hedström (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2012)
This study investigates mechanisms of tie formation in an interorganizational network generated by the mobility of employees between organizations. We analyze a data set that contains information on all organizations in the Stockholm metropolitan area between 1990 and 2003. We show that the formation of new ties is contingent upon the direction of past ties, and that most connections occur at an intermediate geodesic distance of 2 and 3. The findings highlight the importance of tie direction and indirect connections in research on network dynamics and knowledge exchanges stemming from the mobility of employees across organizations.
Keywords: Z13; 330; labor markets; mobility; interorganizational network; information flow; directed ties; Wissenstransfer; Soziales Netzwerk; Arbeitsplatzwechsel; Schweden